Magic wand :play magically in a scientific way - Nuzhat, Sabrina; Marzana Binte Amin; Sadia, Farhana Zainab; Rahman, Sakib (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.